Protective Potential of Antioxidant Enzymes as Vaccines for Schistosomiasis in a Non-Human Primate Model - Carvalho-Queiroz, Claudia; Nyakundi, Ruth; Ogongo, Paul; Rikoi, Hitler; Egilmez, Nejat K.; Farah, Idle O.; Kariuki, Thomas M.; LoVerde, Philip T. (Frontiers in Immunology, 2015)
Schistosomiasis remains a major cause of morbidity in the world. The challenge today is not so much in the clinical management of individual patients, but rather in population-based control of transmission in endemic areas. Recent large-scale efforts aimed at limiting schistosomiasis have produced limited success. There is an urgent need for complementary approaches, such as vaccines. We demonstrated previously that anti-oxidant enzymes such as Cu-Zn superoxide dismutase (SOD) and glutathione S peroxidase (GPX), when administered as DNA-based vaccines induced significant levels of protection in inbred mice, greater than the target 40% reduction in worm burden compared to controls set as a minimum by the WHO. These results led us to investigate if immunization of non-human primates with antioxidants would stimulate an immune response that could confer protection, as a prelude for human trials. Issues of vaccine toxicity and safety that were difficult to address in mice were also investigated. All baboons in the study were examined clinically throughout the study and no adverse reactions occurred to the immunization. When our outbred baboons were vaccinated with two different formulations of SOD (SmCT-SOD and SmEC-SOD) or one of GPX (SmGPX), they showed a reduction in worm number to varying degrees, when compared with the control group. More pronounced, vaccinated animals showed decreased bloody diarrhea, days of diarrhea and egg excretion (transmission), as well as reduction of eggs in the liver tissue and in the large intestine (pathology) compared to controls. Specific IgG antibodies were present in sera after immunizations and 10 weeks after challenge infection compared to controls. PBMC, mesenteric and inguinal node cells from vaccinated animals proliferated and produced high levels of cytokines and chemokines in response to crude and recombinant antigens compared with controls. These data demonstrate the potential of antioxidants as vaccine candidates.